Comparative between takaful and insurance in fiqh / Adib Iliya Abdul Ghani … [et al.] - Abdul Ghani, Adib Iliya; Abu, Muhammad Najmi; Shuhaimi, Muhammad Haziq Luqman; Wan Razali, Wan Fakrulrazi; Zabidi, Muhammad Firdaus; Mahmud, Abdul Razak (2023)
Takaful (Islamic insurance) is an alternative concept to conventional insurance, which is prohibited by Sharia because it contains elements of usury (riba), features of significant uncertainty (gharar) and gambling (maysir). This study examines the issue and comparison between takaful and conventional insurance which is emphasized in its use in Islamic practice as well as the views of contemporary scholars regarding the issue and law of the use of takaful and conventional insurance in this modern era. This comparison also explains the good and bad elements in the use of takaful and conventional insurance methods. The study suggests that the takaful model, structured around the concept of mutual aid, such as the one based on the principle of tabarru', can eliminate all usury arising from the conventional nature of insurance exchanges. The study concludes with a set of actionable policy recommendations. It also gives deeper knowledge about the big difference and its impact on the Islamic financial world, which has more and more challenges that must be overcome, in order to protect the interests of Muslims, so that they can live their daily lives by following everything that Allah S.W.T has commanded and avoiding all His prohibitions.